Sosialisasi Penggunaan Portabel Alat Pemantauan Suhu, Kelembaban dan Gas Ammonia Kandang Ayam Broiler Pada UKM Peternakan Hasanah - Mochamad Irwan Nari; Azamataufiq Budiprasojo; Nur Muhamad (Journal of Community Development, 2025)
UKM Peternakan Hasanah is a broiler chicken farming business with a closed house system established in 2022 in Sumber Baru Village, Jember Regency. This farm raises 10,000 chickens with a harvest period at the age of 28 to 32 days. One of the main problems is manual monitoring of temperature, humidity, and ammonia gas, resulting in a lack of precision and efficiency. As a solution, technology is applied in the form of a portable monitoring tool using a DHT22 sensor for temperature and humidity and an MQ137 sensor for ammonia gas. Data from the sensor is processed with ESP32 and stored on a microSD card. The implementation method used is Participatory Learning and Action (PLA), which involves partners in every stage, from situation analysis, tool making, mentoring, to evaluation. This program produces a monitoring tool that is cheap, portable, and easy to use, with an increase in partner understanding from 30% to 80%. As a result, the chicken mortality rate has decreased and the efficiency of cage management has increased. This program is expected to become a model for sustainable technology for broiler chicken farming in Indonesia.